Signs and signals limiting myocardial damage using PICSO: a scoping review decoding paradigm shifts toward a new encounter - Mohl, Werner; Kiseleva, Zlata; Jusic, Alem; Bruckner, Matthäus; Mader, Robert M. (Frontiers in Cardiovascular Medicine, 2023)
Therapeutic success inducing myocardial recovery in acute coronary syndromes (ACS) is limited to a timely and effective reopening of infarct vessels. Cardiac microcirculation has only recently become the focus of a therapeutic target to improve cardiac performance. Clinical observations in ACS patients indicate that PICSO (pressure-controlled intermittent coronary sinus occlusion), a trans-coronary sinus intervention, induces myocardial recovery by changing flow and pressures in cardiac veins. Here, we assess the paradigm shift between the dose-response dependent effects of PICSO on infarct size and molecular implications. Previous findings relate hemodynamic PICSO effects in cardiac veins to myocardial salvage and upregulation of vasoactive molecules in ischemic myocardium. Verifying our theory of "embryonic recall," the previously published upregulation of miR-19b and miR-101 significantly correlates to the time of pressure increase in cardiac veins during PICSO (r²=0.90 p<0,05; r2=0,98 p<0,03), suggesting a flow and pressure-dependent secretion of signaling molecules into the coronary circulation. MiR-145-5p, a flow-sensitive signaling molecule, is selectively a fivefold increase in porcine myocardium subjected to PICSO. Furthermore, the known effect of cardiomyocyte proliferation by miR-19b, and the protective role of miR-101 against remodeling, show another potential interaction of PICSO in patients with ACS. Moreover, molecular PICSO effects in ACS patients may contribute to the well-established effects of redistributing venous flow towards deprived myocardium and clearing the ischemic, reperfused cardiac microcirculation. A burst of specific microRNA reiterating embryonic molecular pathways may play a role in targeting myocardial jeopardy and will be an essential therapeutic contribution in limiting infarcts in recovering ACS patients.